Gerakan Pendampingan 1000 Hari Pertam Kehidupan (HPK) sebagai Upaya Pencegahan Stunting di Kelurahan Uma Sima, Kabupaten Sumbawa Besar - Yunita Lestari; Has’ad Rahman Attamimi; Iga Maliga (Jurnal Kabar Masyarakat, 2026)
Stunting remains a major nutritional problem in many priority intervention areas, particularly among mothers and children during the First 1,000 Days of Life (1,000 HPK), a critical period that determines children's growth and development. Limited knowledge regarding nutrition, appropriate parenting practices, and optimal infant and young child feeding contributes significantly to the high prevalence of stunting. This community service program aimed to improve community knowledge and behavior related to stunting prevention through the implementation of the First 1,000 Days of Life (1,000 HPK) mentoring program. The intervention employed health education and home-visit mentoring as its primary methods. The target participants included pregnant women, breastfeeding mothers, postpartum mothers, and mothers with children aged 0–2 years residing in a stunting-priority area.The community service program was successfully implemented in Uma Sima Village. Educational activities effectively enhanced participants' understanding of the importance of adequate nutrition, exclusive breastfeeding, and regular child growth and development monitoring. Among the 27 participants, one child was identified as experiencing stunting, indicating the need for continuous and comprehensive follow-up assistance. The high level of community participation and enthusiasm throughout the program demonstrated that health education and mentoring are valuable strategies for increasing public awareness and strengthening stunting prevention efforts during the First 1,000 Days of Life.